2010
DOI: 10.1016/j.dnarep.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Conserved helicase domain of human RecQ4 is required for strand annealing-independent DNA unwinding

Abstract: Humans have five members of the well conserved RecQ helicase family: RecQ1, Bloom syndrome protein (BLM), Werner syndrome protein (WRN), RecQ4, and RecQ5, which are all known for their roles in maintaining genome stability. BLM, WRN, and RecQ4 are associated with premature aging and cancer predisposition. Of the three, RecQ4's biological and cellular roles have been least thoroughly characterized. Here we tested the helicase activity of purified human RecQ4 on various substrates. Consistent with recent results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(119 citation statements)
references
References 66 publications
3
115
0
1
Order By: Relevance
“…We also take into consideration the probable role of post-translational modification on the helicase activity of RECQL4. Unlike our study, most previous reports used bacterial expression system for purification (6,7). Furthermore, another study using baculovirus system purified human RECQL4 also showed relatively weaker helicase activity (5).…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…We also take into consideration the probable role of post-translational modification on the helicase activity of RECQL4. Unlike our study, most previous reports used bacterial expression system for purification (6,7). Furthermore, another study using baculovirus system purified human RECQL4 also showed relatively weaker helicase activity (5).…”
Section: Discussionmentioning
confidence: 45%
“…However, robust ATP-dependent helicase activity for human RECQL4 has not been demonstrated for substrates with double-stranded regions longer than 22 bp (3,(5)(6)(7)30). Typically demonstration of strand exchange activity has been reported for substrates with longer double-stranded regions in the presence of excess single-stranded traps.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations